Peran Wagner Group dalam Pemenuhan Kepentingan Nasional Rusia dalam Operasi Militer Khusus di Ukraina - Siti Nurhaliza; Burhanuddin, Agussalim (Jurnal Ilmu Sosial dan Humaniora, 2023)
Abstract Since Russian President, Vladimir Putin, carried out a "special military operation" to Ukraine on February 24, 2022, Russia is actively using the services of the Wagner Group, one of the Private Military Companies (PMC) to control several cities in Eastern Ukraine such as Soledar City and Bakhmut City. Even though Russia and the Wagner Group did not show official relations, the emergence of the PMC as a non-state actor gave rise to another discourse on the study of international security and conflict. This study aims to explain the relationship between Russia and Ukraine with principal-agent theory through several questions such as, what is the existence of PMC in Russia, what was the relationship between Russia and the Wagner Group before the Russia-Ukraine conflict in 2022, and how is the output given by the Wagner Group to Russia in the 2022 Russia-Ukraine conflict. In this study, the author uses a qualitative research method that collects data in the form of articles and online links to then analyze it explanatorily. The results of this study are that Russia is increasingly actively using PMC services as a result of the Gerasimov Doctrine in 2014 even though PMC status in Russia remains illegal and the Wagner Group has become a prominent PMC since the annexation of Crimea in 2014 and its involvement in the Russia-Ukraine conflict in 2022. Analysis of relations between Russia and The Wagner Group through principal-agent theory shows that there is a relationship due to the desire to fulfill the national interests of Russia and the interests of the company's sustainability from the Wagner Group. Keyword: Private Military Company (PMC), Wagner Group, Russia-Ukraine Conflict, Principal-Agent Theory.